GERAKAN SOSIAL TAREKAT IDRISIYYAH; (Melacak Akar Moderasi dalam Konsep Tasawuf Sanusiyyah) - Munir, Asep (Siyasyatuna | Jurnal Hukum Tata Negara, 2021)
Simplification and generalization of Sufism as a scourge of backwardness of Islamic civilization is a non-objective rationalization effort. This is because, with no intention of covering up the existing realities, Sufism as a pro-active, responsive, and progressive social movement to the demands of urgent social change is also found in its presence in filling the empty recesses left by other variants of Sufism. One of them is the Idrisiyyah/Sanusiyyah congregation, which is thought to reflect the methodological synthesis of various other special congregations of the congress. It is not surprising that the postulates he builds always presuppose the unification of the two methods of isyraqiyyah and burhaniyyah reasoning in an equal and balanced manner. Apart from that, the suluk etiquette in this tarekat is also very strict in complying with the referential consensus of the Qur'an and As-Sunnah. While religious expression as shown by the factual-objective reality observed, both at the level of doctrine, ritual, and social movement system, it often applies a serious, consistent, and sequential dialectic of faith trilogy, in which the elements are composite of several basic concepts of Science-Worship-Charity, which in turn gave birth to the views, attitudes and social behavior of the pesalik in it which tended to be moderate. At least, the moderate attitude shown appears in what van der leeuw gerardus calls the essence and manifestation which includes two esoteric and exoteric dimensions at once. The first relates to issues of doctrine and rites, while the second relates to the mode of social interaction with all in-group and out-group entities. Therefore, this discussion is important to study because its position is to clarify the problems that surround the character and essence of Sufism itself, through an in-depth study of the Idrisiyyah Order. On the basis of that statement, the issues studied will be limited to two questions, namely; first, how is the history of the development of the Idrisiyyah tarekat movement?; and second, what is the moderate concept of the Idrisiyyah tarekat perspective which is the basis of its movement? Thus, this study will rely on the type of library research with a historical-sociological approach. Meanwhile, primary and secondary data obtained from both channels; Field research and literature studies will